Sonication-Assisted Synthesis of β-Mercuric Sulfide Nanoparticles - Xin Xu; Elizabeth R. Carraway (Nanomaterials and Nanotechnology)
The nanoscale semiconductor β‐mercuric sulphide (HgS) has promising applications in electronic and optical fields. Continued development of synthesis methods is needed to expand approaches that produce uniform particles, while avoiding reagents of high toxicity and ecological impact. A solvent‐based approach was developed using mercuric chloride and elemental sulphur as the mercury and chalcogenide sources. Ethanol was used as the solvent and sodium hydroxide as the hydrolysis reagent. Use of mild sonication resulted in smaller particles (average 11nm diameter) than without sonication treatment (average 17nm diameter) and continuous nitrogen purging reduced the surface oxygen content of the particles from approximately 25% to 6%. Particle characterization methods included TEM, XRD, XPS, UV‐visible absorbance spectroscopy and DLS. The nanoparticles were typically spheres of 10‐15nm in diameter. Aggregates formed in aqueous solutions tended to be in the range of 100nm or more. The overall process can be performed simply at room temperature and is comparatively free of toxic chemical hazards. The process does not include surfactants or other stabilizers that could potentially contaminate the nanocrystals. In principle, the method could be applied to synthesis of other metal chalcogenide nanoparticles.